Occlusal splints in reversible occlusal therapy of craniomandibular dysfunction - Lazić Vojkan; Đorđević Igor; Todorović Ana (Serbian Medical Society - Dental Section, Belgrade, 2011)
Craniomandibular dysfunction (CMD) is a set of structural and functional disorders of different etiology that affects temporomandibular joint (TMJ) and orofacial muscles. The most common etiologic factors are psychogenic, occlusal, trauma and congenital anomalies of craniofacial structures. About 75% of the examined population have mild symptoms of CMD while 3-4% have more severe symptoms which require medical attention. The main symptoms why people seek for medical attention are: facial pain which increases with chewing and irradiates in surrounding areas and pain in TMJ which irradiates in the ear canal, temporal area or neck. Painful restriction of mandible during mouth opening and eccentric movements is frequent as well as mandible deviation or deflection. Sound effects in TMJ such as popping or clicking during mouth opening are common. Initial and least invasive therapeutic procedure is reversible occlusal therapy using splints. There are two main types of occlusal splints: stabilization and relaxation. First type of splints works on condyle stabilization in orthopedically stable position; it is superoanterior condylar position in articular fossa with position of intercondylar discs between condyle and articular fossa when working cusps of the antagonists are in maximal contact with the splint. Another type of splint causes disocclussion of posterior teeth and eliminates negative effects of occlusal interference in the intercuspal position or during eccentric mandibular movements. During therapy, occlusal splint temporarily changes occlusal relationships as well as relations within TMJ, causing reduction of CMD symptoms. The best therapeutic effect for reduction of CMD symptoms is achieved by combination of physical therapy and medication.